Synthesis of antibodies, including antiviral antibodies, in the knee joints of patients with arthritis. Issue 11 (November 1985) - Mims, C A; Stokes, A; Grahame, R
Abstract : Serum and synovial fluids from 16 patients with seronegative arthritis and eight with rheumatoid arthritis were studied for immunoglobulin levels and for antibody levels to five viruses. When allowances were made for the distribution of immunoglobulins between serum and synovial fluid there was evidence that in several patients antibody to one or more viruses was synthesised locally in the joint. IgG and especially IgM were present in greatly increased amounts in arthritic joints compared with normal joints. On the basis of serum/synovial fluid ratios inflammation and local immunoglobulin synthesis are discussed as possible causes. These results are compared with antiviral antibody and immunoglobulin ratios observed in the serum and cerebrospinal fluid of patients with multiple sclerosis.